A tensão pós-moderna no cinema - Maria Helena Braga e Vaz da Costa (Ciências Sociais Unisinos)
Increasing interest in new special effect technologies has fostered new possibilities in the use of cinema apparatuses. Digital as well as other technologies, which have been used to represent illusion, fantasy or realism, have been a feature of contemporary cinema production. The general understanding is that cinema´s strength lies in the possibility of creating images of the real not necessarily the real. This is the key element in the production of meaning, making cinema a signifying system connected to reality. Starting from different theories about the condition of post-modernity, this paper discusses contemporary cinema production by looking at the representation of urban space and violence as well as new paradigms for representing and understanding cultural identity in post-modernity and how we represent it through images